2012
DOI: 10.3762/bjoc.8.169
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic carbene-catalyzed direct cross-aza-benzoin reaction: Efficient synthesis of α-amino-β-keto esters

Abstract: SummaryAn efficient catalytic synthesis of α-amino-β-keto esters has been newly developed. Cross-coupling of various aldehydes with α-imino ester, catalyzed by N-heterocyclic carbene, leads chemoselectively to α-amino-β-keto esters in moderate to good yields with high atom efficiency. The reaction mechanism is discussed, and it is proposed that the α-amino-β-keto esters are formed under thermodynamic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The NHC generated from the bicyclic pentafluoro triazolium salt promoted the chemoselective cross aza-benzoin reaction of aldehydes with N -PMP-imino esters to afford α-amino-β-keto esters in good yield ( Scheme 22 ) [ 38 ]. A range of functional groups are tolerated under the optimised reaction conditions.…”
Section: Reviewmentioning
confidence: 99%
“…The NHC generated from the bicyclic pentafluoro triazolium salt promoted the chemoselective cross aza-benzoin reaction of aldehydes with N -PMP-imino esters to afford α-amino-β-keto esters in good yield ( Scheme 22 ) [ 38 ]. A range of functional groups are tolerated under the optimised reaction conditions.…”
Section: Reviewmentioning
confidence: 99%
“…The cross-aza-benzoin reaction between aldehydes and N-PMP-imino esters 126 was very well promoted by the NHC generated from bicyclic pentafluorotriazolium salt 15 to afford products of -amino--keto esters 127 in good yield, as investigated by Uno and colleagues in 2012 [93]. Scheme 8 depicts their findings.…”
Section: Aza-benzoin Condensationmentioning
confidence: 91%
“…Takemoto et al have reported N -heterocyclic carbene (NHC)-catalyzed acylation of α-imino esers, to synthesize α-amino-β-keto esters. Reactions were carried out by stirring a solution of an aldehyde with 1.1 equiv of α-imino ester in the presence of NHC precatalyst 345a (20 mol %) and K 2 CO 3 (20 mol %) in THF at room temperature for 24 h. Various substituted aromatic aldehydes worked well in the reaction, affording corresponding acylated products 344 in 39–73% yields.…”
Section: Acylationmentioning
confidence: 99%
“…Takemoto et al 138 . 142 Examples of the addition of N, O, and S nucleophiles to αimino esters are rare, and corresponding addition products could be utilized in the heterocycles synthesis.…”
Section: Acylationmentioning
confidence: 99%